Conjugative transposition of the vancomycin resistance carrying Tn1549: enzymatic requirements and target site preferences. Issue 5 (18th January 2018) - Lambertsen, Lotte; Rubio‐Cosials, Anna; Patil, Kiran Raosaheb; Barabas, Orsolya
Summary: Rapid spread of resistance to vancomycin has generated difficult to treat bacterial pathogens worldwide. Though vancomycin resistance is often conferred by the conjugative transposon Tn 1549, it is yet unclear whether Tn 1549 moves actively between bacteria. Here we demonstrate, through development of an in vivo assay system, that a mini‐Tn 1549 can transpose in E. coli away from its natural Gram‐positive host. We find the transposon‐encoded INT enzyme and its catalytic tyrosine Y380 to be essential for transposition. A second Tn 1549 protein, XIS is important for efficient and accurate transposition. We further show that DNA flanking the left transposon end is critical for excision, with changes to nucleotides 7 and 9 impairing movement. These mutations could be partially compensated for by changing the final nucleotide of the right transposon end, implying concerted excision of the two ends. With changes in these essential DNA sequences, or without XIS, a large amount of flanking DNA transposes with Tn 1549 . This rescues mobility and allows the transposon to capture and transfer flanking genomic DNA. We further identify the transposon integration target sites as TTTT‐N6‐AAAA. Overall, our results provide molecular insights into conjugative transposition and the adaptability of Tn 1549 for efficient antibiotic resistance transfer. Abstract : The Enterococcal conjugative transposon Tn 1549 spreads vancomycin resistance between bacteria. Here, we show efficient and accurate movement of a mini‐Tn 1549 version in E. coli and determine that jumping from donor to target DNA site requires specific DNA sequences in the transposon and two transposon proteins XIS and INT. When XIS is absent or mutations occur in the DNA, the transposon transfers additional DNA with it; this rescues transposon movement and mediates transfer of extra DNA.